THE IMPLEMENTATION OF ROLE PLAY WITH VIDEO BLOGS (VLOG) IN TEACHING SPEAKING TO THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL 3 OF PALEMBANG - Miranti Anggun Sapitri; Magdad Hatim; Noviati Noviati (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
Speaking Skill is essential in communication as a foreign language, either in educational qualification or in career achievement. The students have intermediate speaking skill potential to gain further education and to find employment. The problem of this research deals with the fact that most of students are lack of speaking skill. First, particularly the eleventh grade students of Senior High School 3 of Palembang are not motivated to learn and increase their speaking skills. Second, consequently the students are not able to act as interlocutors when the communication occurred. The objective of this study was to find out whether or not there is a significant difference of speaking scores of the eleventh grade students taught through Role play with Video blogs (Vlog) from those of the ones taught through a conventional technique at Senior High School 3 of Palembang. This research was True Experimental design (Quantitative). The research was conducted from July to August 2020 by online. The subject of the research was 36 students of the eleventh grade of Senior High School 3 of Palembang. The technique of collecting data used a monologue test. The monologue test was done to know whether there was a significant difference by using role-play with video blogs (vlog) in teaching speaking skill. The students’ average score of the experimental group in the posttest was 53.29 while the students’ average score in the control group was 46.04. Meanwhile the critical value was 0.05 significance level for two-tailed test with 35 (df) was 1.68 since the t-obtained was 11.352, it was higher than the t-table. The result of research showed that there was a significant difference of speaking scores of the eleventh grade students taught through Role-play with Video blog (Vlog) from those of ones taught a conventional technique at Senior High School 3 of Palembang. The use of role play with video blogs (vlog) not only made the students enjoy, fun and relax learning English but also indirectly made the students capable improvise their skill based on their mind.